7. Inhibition Activity of Ethanolic Extract of Binahong Leaf (Anredera cordifolia (Ten.) Steenis) on Staphylococcus aureus Bacteria - Herrialfian Herrialfian; Mizla Maulia Nisya Lubis; Darmawi Darmawi; Maryulia Dewi; Erina Erina; Hennivanda Hennivanda; Abdul Harris (Universitas Syiah Kuala, 2021)
This research aimed to investigate the inhibition activity of ethanolic extract of binahong leaf (Anredera cordifolia (Ten.) Steenis) on Staphylococcus aureus. Bacteria were obtained from the Microbiology Laboratory of Faculty of Veterinary Medicine Unsyiah, isolated from the honey bear (Helarctos malayanus) wound area. This experiment was conducted with re-identification of the bacteria before treatment. Afterward, the bacteria were treated with ethanolic extract of binahong leaf with a concentration of 20%, 40%, 60%, and 80% by using the disc diffusion (Kirby-Bauer) method. The data were analyzed descriptively by measuring and comparing the inhibition zone among treatments. The results showed that the treatment could inhibit the growth of Staphylococcus aureus, however, the inhibition zone was narrow with a mean diameter of 20% was 6.8 mm, 40% was 7.4 mm, 60% was 8.2 mm, and 80% was 8.1 mm. It can be concluded that ethanolic extract of binahong leaf had comparative inhibition activity toward Staphylococcus aureus.